A descriptive analysis of Shariah-compliant digital payment usage among Generation Z in Malaysia - Musaddad, Hafirda Akma; Wan Mohd Assrudin, Wan Anis; Amar, Siti Noradiah; Mokhtar, Nurmasturah; Mohd Jamalludin, Muhamad Fhadli Syakirin; Che Mat Razali, Nur Akmarini; Abu, Masyitah (Journal of Islamic, Social, Economics and Development, 2026)
The rapid growth of digital payment technologies has accelerated the shift toward cashless transactions, particularly among younger consumers. In Muslim-majority countries such as Malaysia, this development has increased interest in Shariah-compliant payment technology, which emphasises ethical financial practices and adherence to Islamic principles. Despite the prominence of Generation Z as a key user group of digital payments, empirical evidence on how demographic characteristics shape their intention to adopt Shariah-compliant payment technology remains limited. This study aims to examine demographic differences in Generation Z’s intention to adopt Shariah-compliant payment technology in Malaysia. Using a quantitative, survey-based research design, data were collected from 437 Generation Z respondents across Malaysia through an online questionnaire. The data were analysed using SPSS, employing independent sample t-tests, one-way ANOVA, and correlation analysis to assess differences in adoption intention across selected demographic factors, including gender, religion, age, education level, monthly income, ethnic group, and marital status. The findings reveal that adoption intention varies significantly across several demographic categories, indicating that Generation Z is not a homogeneous group in its acceptance of Shariah-compliant payment technology. The results contribute to the existing literature by providing empirical evidence on demographic-based differences in Shariah-compliant PayTech adoption, an area that has received limited scholarly attention. From a practical perspective, the findings offer valuable insights for policymakers, Islamic financial institutions, and PayTech providers in developing targeted strategies and inclusive digital payment solutions that align with the diverse demographic profiles of Generation Z consumers in Malaysia.